(untitled) (Al-Qamar, 2024)
Muhammad Azmat -ul -Allah Khan (1887-1927) is well known geet nigar in urdu history. In critical history of urdu, he is known as dissident of Ghazal. He is remembered to bring change in the meter of urdu poetry. He was an examplary prose writer. His poem and prose both carry variety of theme and contant. He is Known for his modernistic poetry and prasodic expermentations with Urdu poetry. His book Sureelay bol and its preface is an epilome of modern urdu poetry. But article illuminates a hiding aspect of his literary work i.e his role in the formation of Azad Nazam as a lyricist. This article analyzes his role in the formation of Azad Nazam by evaluating his book " Sureelay Bol".